1999
DOI: 10.2337/diabetes.48.12.2367
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of t-SNARE, syntaxin 1, and SNAP-25 in pancreatic beta-cells is involved in impaired insulin secretion from diabetic GK rat islets: restoration of decreased t-SNARE proteins improves impaired insulin secretion.

Abstract: The physiological role of soluble N-ethylmaleimide-sensitive factor attachment protein (SNAP) receptor (SNARE) proteins in insulin exocytosis has been reported in pancreatic beta-cells. To determine whether the beta-cells of GK rats, a nonobese rodent model of type 2 diabetes, exhibit abnormalities in their SNARE proteins, we studied the expression and function of target (t)-SNAREs, syntaxin 1A, and synaptosomal-associated protein of 25 kDa (SNAP-25) in GK rat islets. Although insulin release and insulin conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
140
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(158 citation statements)
references
References 13 publications
12
140
1
5
Order By: Relevance
“…It is of note that the recovery of the decreased number of SNAP-25 clusters in GK beta cells to normal levels by adenovirus treatment or insulin treatment could restore the number of docked insulin granules, which caused an increased number of fusion events from previously docked granules. We previously reported that restoration of decreased t-SNARE levels improved the impaired insulin secretion in GK islets [10]. At that time, however, we could not know how t-SNARE restoration affects the insulin exocytosis.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…It is of note that the recovery of the decreased number of SNAP-25 clusters in GK beta cells to normal levels by adenovirus treatment or insulin treatment could restore the number of docked insulin granules, which caused an increased number of fusion events from previously docked granules. We previously reported that restoration of decreased t-SNARE levels improved the impaired insulin secretion in GK islets [10]. At that time, however, we could not know how t-SNARE restoration affects the insulin exocytosis.…”
Section: Discussionmentioning
confidence: 88%
“…For the normalisation of hyperglycaemia, human insulin (Humalin N; Lilly, Indianapolis, Ala., USA) was injected subcutaneously at 08.00 (2 U/rat) and 20.00 (4 U/rat) hours daily for 2 weeks. Pancreatic islets of Langerhans were isolated by collagenase digestion [10], with some modification. Isolated islets were dissociated into single cells by incubation in Ca 2+ -free KRB containing 1 mmol/l EGTA, and cultured on fibronectin-coated (KOKEN, Tokyo, Japan) high-refractive-index glass (Olympus, Tokyo, Japan) in RPMI 1640 medium supplemented with 10% FBS (Invitrogen Gibco BRL, Carlsbad, Calif., USA), 200 U/ml penicillin, and 200 µg/ml streptomycin at 37°C in an atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations